Enhancing Futsal Game Performance: A Tactical Games Model Implementation Approach - Sucipto Sucipto; Fauzzi Dwi Utomo; Teten Hidayat; Burhan Hambali (TEGAR: Journal of Teaching Physical Education in Elementary School, 2022)
The application of a learning model is one of the variables affecting physical education learning outcomes, both in cognitive, affective, and psychomotor aspects. This study aimed to examine the effect of the tactical game model in improving learning outcomes. The pretest-posttest control group design with experimental method was used in this study. The participants of the study were 20 students who took part in the futsal extracurricular (10 male students and 10 female students). The instrument used in this study was Games Performance Assessment Instrument (GPAI) to measure futsal game performance. Based on data processing and analysis, the following results were found 1) both tactical and conventional learning models had an impact on improving futsal game performance, 2) the tactical game model had a higher and more significant effect than the conventional model on improving the learning outcomes, namely futsal game performance, proven by the results of the N-Gain percentage where the score of the tactical group was 63.5% while the score of the conventional group was 51.6%. Based on the result of the analysis, it implies that both models (tactical and conventional models) have an impact on increasing learning outcomes, specifically in futsal game performance, where the tactical game model has a higher impact and is more effective than the conventional model.